2017
DOI: 10.5539/sar.v6n3p35
|View full text |Cite
|
Sign up to set email alerts
|

Soil and Rhizosphere Bacterial Diversity in Maize Agro- Ecosystem

Abstract: Management practices used in maize production have an impact on soil agro-ecosystems where different microbial communities coexist. Soil inhabiting bacteria are numerous and diverse, but we know very little about their ecological distribution. Here we analyzed the bacterial community diversity in the rhizosphere of two transgenic maize cultivars, in agricultural soil before sowing and in non-cultivated soil in an experimental site in the south region of Uruguay. We followed two culture-independent methods: DGG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Also, metagenomic analysis of wheat plants demonstrated that there was high bacterial diversity in the rhizosphere than in bulk soil (Velázquez-Sepúlveda et al 2012). In addition, during the initial stages of maize growth, several studies based mainly on selected rhizospheric isolates also reported higher bacterial diversity and stated that the rhizosphere of small plants is a more unpredictable ecosystem than the rhizosphere of mature plants (Rodriguez et al 2017). García-Salamanca et al (2013) observed in accordance with the assumption that the rhizosphere is more nutrientrich than bulk soil; the levels of activity of alkaline phosphatase, β-glucosidase and dehydrogenase enzymes from bacterial cells in the maize rhizosphere were higher than the same enzymatic activity tested in bulk soil.…”
Section: Effects Of Soil Parameters On the Bacterial Community Structure And Functional Diversitymentioning
confidence: 99%
“…Also, metagenomic analysis of wheat plants demonstrated that there was high bacterial diversity in the rhizosphere than in bulk soil (Velázquez-Sepúlveda et al 2012). In addition, during the initial stages of maize growth, several studies based mainly on selected rhizospheric isolates also reported higher bacterial diversity and stated that the rhizosphere of small plants is a more unpredictable ecosystem than the rhizosphere of mature plants (Rodriguez et al 2017). García-Salamanca et al (2013) observed in accordance with the assumption that the rhizosphere is more nutrientrich than bulk soil; the levels of activity of alkaline phosphatase, β-glucosidase and dehydrogenase enzymes from bacterial cells in the maize rhizosphere were higher than the same enzymatic activity tested in bulk soil.…”
Section: Effects Of Soil Parameters On the Bacterial Community Structure And Functional Diversitymentioning
confidence: 99%